Phenotyping for QTL identification: A case study of resistance to Plasmopara viticola and Erysiphe necator in grapevine - Possamai, Tyrone; Wiedemann-Merdinoglu, Sabine (Frontiers in Plant Science, 2022)
Vitis vinifera, the most cultivated grapevine species worldwide, is susceptible to Plasmopara viticola and Erysiphe necator, the causal agents of grape downy and powdery mildew (DM and PM). Current strategies to control DM and PM diseases mainly rely on agrochemical treatments. Breeding for resistant varieties, by the introduction of resistance loci from wild Vitis spp., represents an alternative solution to the recurrent use of fungicides. During the last two decades, 33 loci of resistance to P. viticola (Rpv) and 15 loci of resistance to E. necator (Ren and Run) have been identified. Phenotyping strongly influences the QTL detection and characterization and currently result in the main bottleneck in the research of Rpv and Run/Ren loci. The aim of this article is to review the phenotyping strategies implemented in mapping studies to date. Resistance evaluations take place in different environments such as the field, the greenhouse and the laboratory. A detailed analysis of the methods used, shows that, whatever the level of phenotyping, some elements can be considered as sources of variation. The environmental conditions, the plant material (organ physiology and age), the inoculum (genetic and origin) and pathogen inoculation (natural or controlled), and the assessment method (date, frequency and method of scoring) affect the resistance assessment and the quality of data. Regarding these elements, providing minimal information on phenotyping experiments should enhance the accuracy and reliability of data and participate in a better standardization and replicability of resistance evaluation protocols.